Polymeric nanoparticles for colon cancer therapy: overview and perspectives. Issue 48 (23rd November 2016) - You, Xinru; Kang, Yang; Hollett, Geoffrey; Chen, Xing; Zhao, Wei; Gu, Zhipeng; Wu, Jun
Abstract : Colorectal cancer (CRC) is the third-most common malignant tumour and is associated with high morbidity and mortality worldwide. Abstract : Colorectal cancer (CRC) is the third-most common malignant tumour and is associated with high morbidity and mortality worldwide. This review summarizes the recent progress in the development of polymeric nanoparticle systems for colon cancer therapy.